"Eficacia de los ejercicios básicos del método méziéres para mejorar la postura corporal en adultos mayores del centro gerontológico cantón Chambo, periodo agosto 2015 a enero 2016” - Guaño Ayala, Alexander Israel (2017)
The objective of this research is "Demostrate the Effectiveness of the Basic Exercises of the Mezieres Method to Improve the Body Posture in Adults Older, in the Gerontological Center, from Chambo Canton in the Period August 2015 to January 2016". This is an experimental study as it is working with a sample of 50 patients. The methodology was supported by a quasi-experimental design, the types of research correspond to inductive, Field and documental process, whose research design has a Descriptive level. Observation technique was used which allowed us to obtain real information of the characteristics of an object social or natural phenomenon that occurs in the environment. This observation will be made using the evaluation form. Within the presentation and discussion of results, data obtained by observation sheet to be tabulated and organized in tables and atatistical graphs with their respective percentages were processed. As a primary result we obtained better postural reeducation with greater flexibility, increased joint movility and control of breathing in 46% in men and 44% in women. In conclusion, the efficacy of the exercises of the Mézieres Method to improve body posture in older adults was demonstrated, allowing the development of activities od daily living. The treatment protocol lasted 6 months, the estimated time of therapy is 45 minutes to 1 hour approximately, the exercise sequence will be performed as follows: each exercise will have a succession of 5 sets - 10 repetitions with a Slow pace and at each interval of 10 seconds, maintaining adequate breathing control in each patient.